The Relationship Between Parental Knowledge And Parenting Styles With The Occurrence Of Sibling Rivalry In Toddlers In RW 011 Kebayoran Lama Utara, South Jakarta - Fahira, Alya Hanifa; Susanti, Dewi; Junalia, Elly (Sean Institute, 2024)
Sibling rivalry is a common phenomenon in families with more than one child. Unresolved conflicts can lead to emotional disturbances and affect the psychological development and social relationships of the child in the future. Parenting styles not only influence the individual life of the child but also the relationship between siblings. Parental knowledge is crucial in applying effective and appropriate parenting styles, thus managing sibling rivalry and fostering harmonious relationships among children. The purpose of this study is to determine the relationship between parental knowledge and parenting styles with the occurrence of sibling rivalry in toddlers in RW 011 Kebayoran Lama Utara, South Jakarta. The study design is descriptive-analytic with a cross-sectional approach. The population in this study consists of parents with toddlers, totaling 237 individuals. The sample consists of 70 respondents obtained using purposive sampling techniques. The instruments used are a questionnaire on knowledge about sibling rivalry, the Parenting Styles and Dimension Questionnaire Short Version (PSDQ-SV), and sibling rivalry incidents. Bivariate analysis results indicate a relationship between knowledge and the occurrence of sibling rivalry (p-value = 0.003) and a relationship between parenting styles and the occurrence of sibling rivalry (p-value = 0.001). The results of this study are expected to help parents understand the behavior and emotional needs of children in creating a harmonious family environment.